Β-Natriuretic Peptide Level as a Predictor for the Severity of LV Dysfunction - Nasser, Tharwet H.; El-Yassin, Hedef Dhafir; Yakoob, Sabbah (Journal of the Faculty of Medicine Baghdad, 2008)
Background: B -Natriuretic peptide is a neurohormone normally synthesized in ventricular heart muscle and known to be released in situations when left ventricular wall stress increases, it has a variety of physiological functions on its own, that are thought to be compensatory. Objective: The aim of this study was to apply B-natriuretic peptide (BNP) as a biomarker and to correlate its levels with the severity of heart failure using certain selected parameters as indicators of cardiac function. Patients and Methods Forty Six (46) patients with provisional diagnosis of heart failure were chosen for this work, thirty six (36) males and ten (10) Females, their age ranged between 33 and 80 Years. All underwent complete physical examination and ECG tracing together with ECHO/DOPPLER examination for heart failure. Eleven (11) healthy Subjects were chosen as control group for purpose of comparison. The patients were divided into groups, according to Age , Gender, BMI, whether they had the following selected associated diseases: (IHD, hypertension, and diabetes mellitus), smoking habit, Drugs intake, cardiac chambers dilatation including (LV in systole and diastole, RV, and LA), EF%, FS%, degree of diastolic impairment, LV Segmental wall motion abnormalities. Five ml (5ml) specimen of venous blood were aspirated from each patient, and also the control group for estimation of BNP level, using ELIZA technique. Results There was a significant difference in mean serum BNP levels between cases of congestive heart failure and control group. Considering the subject as a positive for heart failure if his BNP level was ≥ 375pmol/l, at this cutoff value there will be a sensitivity of 80.4% and specificity of 100%. Also the study showed highest values of mean BNP in those patients having restrictive pattern of diastolic dysfunction. Conclusion: BNP was used as a biomarker for the first time in Iraq to diagnose congestive heart failure. The role of BNP as a guide to determine the severity of heart failure and the efficacy of treatment was promising, so BNP fulfill most of the criteria in patients with suspected heart failure. At this point it was found that the mean of the right ventricular dimensions were significantly higher in the group with highest BNP quartile compared to lowest quartile BNP group, probably reflecting more severe form of impaired cardiac function and heart failure, a finding which has not been mentioned in any earlier studies in the same field.